SYSTEM ENGINEERING APPROACH TO BUILD AN INFORMATION SYSTEM FOR EMERGENCY CESAREAN DELIVERIES - Lee, Gyu M (International Journal of Industrial Engineering: Theory, Applications and Practice, 2014)
The human is an imperfect being so that he/she has a limitation in perceiving the situations appropriately and making a right decision quickly. Oftentimes, his/her perceptions and decisions come from the individual experiences and characteristics. This vulnerability leading the frequent errors or mistakes aggravates things in an emergency situation of time pressure and complex confusions. In a situation where an emergency cesarean delivery (ECD) is required, the immediate and right medical cares are very important to the fetus and the mother. However, the number of obstetrics doctors is decreasing in recent days and more medical staffs are currently in a great need to treat the high-risk pregnant women. The American College of Obstetricians and Gynecologists established in 1989 that hospitals with obstetric services should have the capability to begin an ECD within 30 minutes of the decision to do so. This goal places intense time pressure on the preparation and surgical teams. We created a team of engineering students and faculty from Pusan National University and health care providers from Pusan National University Hospital in Busan, Korea, set about developing a distributed, mobile communication and information system to facilitate ECDs at Pusan National University Hospital. The resulting prototype ECD Facilitator will be demonstrated to the staff at the hospital and their responses will be collected to see that such a system would reduce the decision-to-incision intervals (DII) to well below the 30-minute ACOG guideline and reduce the likelihood of human errors that compromise patient safety. In future, the developed system would be readily adaptable to other emergency disastrous situation